Author Correction: Behaviour reactions of bottlenose dolphins (Tursiops truncatus) to multirotor Unmanned Aerial Vehicles (UAVs) - Ticiana Fettermann; Lorenzo Fiori; Martin Bader; Ashray Doshi; Dan Breen; Karen A. Stockin; Barbara Bollard (Scientific Reports, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.